‘Farming Writing’: An Innovative Subgenre of Internet Literature - Wang, Aiqing (Humanis; Vol 25 No 4 (2021)DO - 10.24843/JH.2021.v25.i04.p01, 2021)
As an innovative subgenre of Internet literature, ‘farming writing’ has attained popularity in contemporary China’s cyberspace, which, in a narrow sense, denotes narratives pertaining to agronomic theories and agrarian practices. Disparate from cliché-ridden web romances that deploy authorial ‘golden finger’ to equip protagonists with impeccable demeanour and prowess, ‘farming’ fiction is characterised by reality-oriented, detail-enriched depictions, notwithstanding its essence as ‘feel-good writing’. Furthermore, ‘farming’ works are marked by a slow pace, peaceful setting and plain theme, enabling readers to identify with characters and escape from reality. In this article, I scrutinise a ‘farming’ novel under the genre of danmei (aka Boys Love), and further posit that the popularity of ‘farming writing’ is also attributed to the Chinese ethnicity’s devotion to agriculture since time immemorial.